Conjoint Measurement- for Quantifying Judgmental Data - Green, Paul E.; Rao, Vithala R. (Journal of Marketing Research, 1971)
Conjoint measurement is a new development in mathematical psychology that can be used to measure the joint effects of a set of independent variables on the ordering of a dependent variable. In this (primarily expository) article, the techniques are applied to illustrative problems in marketing. In addition, a number of possible areas of application to marketing research are discussed, as well as some of the methodology's limitations.